A Novel Method for Real‐Time Atrial Fibrillation Detection in Electrocardiograms Using Multiple Parameters. Issue 3 (20th November 2013) - Du, Xiaochuan; Rao, Nini; Qian, Mengyao; Liu, Dingyu; Li, Jie; Feng, Wei; Yin, Lixue; Chen, Xu
<x xml:space="preserve">Abstract</x> Background Automatic detection of atrial fibrillation (AF) in electrocardiograms (ECGs) is beneficial for AF diagnosis, therapy, and management. In this article, a novel method of AF detection is introduced. Most current methods only utilize the RR interval as a critical parameter to detect AF; thus, these methods commonly confuse AF with other arrhythmias. Methods We used the average number of f waves in a TQ interval as a characteristic parameter in our robust, real‐time AF detection method. Three types of clinical ECG data, including ECGs from normal, AF, and non‐AF arrhythmia subjects, were downloaded from multiple open access databases to validate the proposed method. Results The experimental results suggested that the method could distinguish between AF and normal ECGs with accuracy, sensitivity, and positive predictive values (PPVs) of 93.67%, 94.13%, and 98.69%, respectively. These values are comparable to those of related methods. The method was also able to distinguish between AF and non‐AF arrhythmias and had performance indexes (accuracy 94.62%, sensitivity 94.13%, and PPVs 97.67%) that were considerably better than those of other methods. Conclusions Our proposed method has prospects as a practical tool enabling clinical diagnosis, treatment, and monitoring of AF.